Drug Delivery Applications of Starch Biopolymer Derivatives - Chen, Jin; Chen, Ling; Xie, Fengwei; Li, Xiaoxi (Springer Nature Singapore : Imprint: Springer, 2019)
This book summarizes the recent advances in applications of starch in state-of-the-art drug carriers (hydrogel, micro- and nano-particulate carriers) with stimulus-responsive and target-specific properties. It also highlights the role of starch and its derivatives in transmucosal administration to improve the bioavailability of drugs. Further, it outlines the principles of effective, advanced, starch-based drug delivery systems and illustrates how these principles are key to the development of future drug delivery strategies. This interesting reference resource is useful for students, researchers and engineers in the fields of carbohydrate chemistry, polymer sciences and drug delivery.